Interplay of Maternal Nutrition, Sanitation, and Socioeconomic Factors in Childhood Stunting across Resource-Limited Rural Communities : A Systematic Review - Mutawaffika Mahir; Asrita Suri; Andi Muh. Ariansyah Nazaruddin (International Medical Journal Corp. Ltd, 2025)
Introduction: Childhood stunting remains a critical public health challenge in resource-limited rural communities, affecting nearly 150 million children under five globally. The interplay between maternal nutrition, sanitation, and socioeconomic factors is complex and context-dependent, with previous studies showing inconsistent results regarding the effectiveness of isolated interventions. Methods: This systematic review synthesized findings from 80 studies examining the interplay of maternal nutrition, sanitation, and socioeconomic factors on childhood stunting in resource-limited rural settings across Sub-Saharan Africa, South Asia, Southeast Asia, and Latin America. Included studies comprised cluster-randomized controlled trials, and country-level decomposition analyses. Results: Maternal nutrition interventions demonstrated consistent positive effects on linear growth across diverse settings, with effect sizes ranging from 0.13 to 0.38 increases in length-for-age Z-scores (1-3,14). In contrast, household-level WASH interventions showed minimal effectiveness on stunting despite high adherence, with three major trials reporting null effects (1-3). Socioeconomic factors, particularly maternal education and household wealth, emerged as dominant determinants, explaining 24.7% of stunting reduction in Nepal and 19.5% in Peru (5,7). Country-level decomposition analyses revealed context-specific drivers: malaria control dominated in Uganda (35%) and Senegal (35%) (4,13), while agricultural productivity accounted for 32% of improvements in Ethiopia (6). Combined WASH and nutrition interventions provided no additive benefit over nutrition alone in major trials (1-3), though integrated programs in Ethiopia showed significant effects (OR: 0.50) (11). Discussion: The discrepancy between strong observational associations and null trial results for WASH interventions suggests substantial confounding by socioeconomic status. Nutrition interventions operate through direct biological pathways addressing micronutrient deficiencies, showing consistent but modest effects. Socioeconomic factors represent long-term structural determinants operating through multiple mechanisms including improved feeding practices, healthcare utilization, and intergenerational transmission. Context-specific determinants—including malaria control, agricultural productivity, and education—must guide intervention priorities. Conclusion: Effective stunting reduction in resource-limited rural settings requires context-specific strategies prioritizing proven nutrition interventions alongside long-term investments in socioeconomic development. WASH interventions should not be abandoned but require more comprehensive community-level approaches rather than household-level infrastructure provision alone. Multisectoral coordination addressing context-specific dominant drivers is essential for sustainable progress.